Correlation of international prostatic symptom score with prostate volume - Raza, Iffat; Mohiuddin, Maria; Ahmed, Syeda Bushra; Lakhani, Mubina; Mukhtar, Sahrish; Hassan, Nuzhat (Journal of Rawalpindi Medical College, 2023)
Objective: To evaluate the correlation of International Prostatic Symptom Score with Prostate Volume of Benign Prostatic Hyperplasia patients. Study Design: A Cross- out sectional study was done. Qualitative variables measured by Chi square test and quantitative by ANOVA. Pearson correlation & multinominal regression were applied. P value considered significant at <0.05. It was conducted in a tertiary care hospital, Ziauddin University Hospital Karachi. Methodology: The data was collected from 103 Benign prostatic hyperplasia patients. Prostate Volume of BPH patient were recorded by transabdominal ultrasonography in Radiology department. Severity of symptoms were assessed by IPSS questionnaire. Result: Mean IPSS was found out to be ±13.7. Clinical presentation showed hesitancy & nocturia as most frequently occurring symptoms in benign prostatic hyperplasia patient, these symptoms were found to be statistically significant with prostatic volume. Conclusion: IPSS strongly correlated with prostate volume. Irritative voiding symptoms have shown more association with increasing prostate volume. Keywords: Benign Prostatic Hyperplasia, Prostate Volume, International Prostatic Symptom Score, Lower Urinary Tract Symptoms.